EFFECTIVENESS AND TOLERABILITY OF TOCILIZUMAB IN PATIENTS WITH RHEUMATOID ARTHRITIS REFRACTORY TO CONVENTIONAL DISEASE MODIFYING ANTI RHEUMATIC DRUGS THERAPY - Kamal, Musharaf; Naeem, Awais; Taqweem, Muhammad Amjad; Salahuddin, Ghazi; Muhammad, Atta; Khan, Zahid Ullah (Journal of Postgraduate Medical Institute, 2020)
Objective: To find out the effectiveness and tolerability of tocilizumab in the treatment of rheumatoid arthritis (RA) patients refractory to conventional disease modifying anti-rheumatic drugs (DMARDS). Methodology: This cross-sectional study was conducted in the department of medicine, Lady Reading Hospital, Peshawar from September 2017 to March 2018. It included 84 patients with diagnosed RA who were refractory to conventional DMARDs therapy. Tocilizumab was given to all patients along with methotrexate (MTX) and low dose prednisolone. Effectiveness of tocilizumab therapy was evaluated by Disease Activity Scale version 28 (DAS- 28) score before and 3 after months of the end of the 3rd dose of tocilizumab. Drug tolerability was assessed by recording the early and late adverse events. Data was analyzed with SPSS version 20. Frequency and percentage were expressed for categorical variables, while mean ± SD were used for numerical variables. Results: The response was more significant in female patients (about 70%) as compared to male patients (50%). Infusion-related allergic reactions were observed only in 2 patients. Headache was more significant which was observed in 6 patients. Overall adverse events in the form of allergy, headache, diarrhea, upper respiratory symptoms, gastritis, and oral ulcers were observed in about 24.8 % of patients. Leukopenia was observed in 4.7% but no life-threatening cytopenias or severe allergic adverse reactions were noted. Conclusion: Tocilizumab is effective and tolerable therapeutic addition in the treatment of patients with rheumatoid arthritis who are refractory to the conventional DMARD treatment.